Clinical-psychopathologic and pathophychological features of adaptation disorders in computer addicted individuals - Starodubtseva, Yuliia (ScienceRise: Medical Science, 2018)
The aim. Comprehensive study of clinical, psychopathological and pathopsychological features of adaptation disorders in persons with computer addiction. Materials and methods. 147 patients with adaptation disorders (F43.21, F43.22). The main group consisted of 85 patients with signs of computer addiction according to the results of AUDIT-like tests, the control group - 62 patients with no signs of addictive behavior. The average age of the patients was 27.0 ± 3.0 years. Methods of the research: clinical and anamnestic; clinical-psychopathological, using AUDIT-like tests for a comprehensive assessment of addictive status (Linsky I.V., Minko A.I., Artemchuk A.P., et al., 2009); psycho-diagnostic using the hospital anxiety and depression scale (HADS) (Zigmond A.S., Snaith R.P., 1983); Clinical scales of anxiety and depression by Hamilton (M. Hamilton, 1967), adapted to ICD-10 (G. P. Panteleeva, 1988) (HDRS) scales of situational and personal anxiety by C. D. Spielberger (in adaptation by Yu. L. Khanin, 1981); enquirer of neuro-psychological stress by Nemchin T.A. (1984); statistical. Results of the research. The structure of computer addiction in the main group of surveyed was as follows: intrusive surfing (46.2 %), computer games (22.3 %); virtual dating (6.4 %); passion for online gambling (13.7 %); cybersex (1.4 %). Depression of mood dominates in the clinical picture of eradication adaptation in persons with computer addiction; internal stress with inability to relax; increased susceptibility to previously neutral stimuli; irritability; asthenic symptoms; loss of interest in work or school, family and friends; sleep-wake cycle disorders. According to the psychodiagnostic examination data, the main group of examined showed clinical signs of anxiety and depression on a hospital scale; severe depressive and disturbing episodes on the Hamilton scale; high drop situational and personal anxiety according to the method of C. D. Spielberger, a high level of severity of neuropsychic stress on a scale T.A. Nemchin. Conclusions. For the clinical picture of adaptation disorders in individuals with computer addiction, a characteristic is decreased mood background; irritability, tendency to affects; disturbing manifestations; hyperesthesia; sleep-wake cycle disorders; clinical manifestations of anxiety and depression on the HADS scale; severe depressive and disturbing episodes on the HDRS scale; high drop situational and personal anxiety; excessive mental stress